2005
DOI: 10.1002/ijc.21422
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration and gene expression in response to tumor hypoxia

Abstract: Monocytes are recruited into tumors from the circulation along defined chemotactic gradients and they then differentiate into tumor-associated macrophages (TAMs). Recent evidence has shown that large numbers of TAMs are attracted to and retained in avascular and necrotic areas, where they are exposed to tumor hypoxia. At these sites, TAMs appear to undergo marked phenotypic changes with activation of hypoxia-inducible transcription factors, dramatically upregulating the expression of a large number of genes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 91 publications
0
143
1
3
Order By: Relevance
“…69, 70). As a consequence, tumor-associated monocytes/macrophages undergo marked phenotypic changes with activation of hypoxiainducible factor 1a, dramatically up-regulating the expression of a large number of genes encoding mitogenic, proangiogenic, and prometastatic cytokines, enzymes, and bioactive lipids (70,71). Interestingly, in vivo and in vitro studies have shown that VEGF, MMPs, and IL-6 in the tumor microenvironment inhibit the differentiation and maturation of dendritic cells and switch their differentiation toward the macrophage lineage (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…69, 70). As a consequence, tumor-associated monocytes/macrophages undergo marked phenotypic changes with activation of hypoxiainducible factor 1a, dramatically up-regulating the expression of a large number of genes encoding mitogenic, proangiogenic, and prometastatic cytokines, enzymes, and bioactive lipids (70,71). Interestingly, in vivo and in vitro studies have shown that VEGF, MMPs, and IL-6 in the tumor microenvironment inhibit the differentiation and maturation of dendritic cells and switch their differentiation toward the macrophage lineage (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, classically activated M1-like TAMs secrete immunostimulatory cytokines that have direct tumoricidal activity. M1-like TAMs, however, are sparse and confined to the less hypoxic regions of tumors (15). The presence of M2-like TAMs in tumors correlates with poor prognosis (16,17), whereas the presence of M1-like TAMs correlates with longer survival for patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells release chemo-attractive factors, such as MCP-1 (monocyte chemotactic protien-1) and RANTES (regulated upon activation, normal T-cell expressed and secreted), and actively recruit leukocytes to tumors [10,11]. Once the bone marrow derived-cells (BMDC) arrive at the tumor site, they contribute to angiogenesis and tumor progression by expressing pro-angiogenic growth factors such as IL-1, VEGF, and IL-8 [7,12].…”
Section: Introductionmentioning
confidence: 99%